A home for Hannah - Lillard, Amy (Lillard, Amy. Pontotoc Mississippi series., 2018)
Fifteen years. That's how long it's been since Hannah McLean set foot in the Amish community where she was raised. Through it all her heart has never forgotten Pontotoc--or Aaron Zook, her first love. Now widowed, and left with little more than her hurting teenager and her prayers, she returns home, even knowing she and her son may be turned away. When Aaron learns Hannah has returned, he nearly falls to his knees. He's a strong man, but lately the care of his three motherless children and family land have been more than he can handle. Now providence has delivered the first woman he loved, and with her, the rush of feelings they once shared.